Physiological and Anatomical Changes of Pregnancy Implications for Anaesthesia - Sarmistha Panigrahi; Sandhya Peethani (Perspective of Recent Advances in Medical Research Vol. 9, 2023)
The purpose of this chapter is to provide detailed information about the physiological and anatomical changes that occur during pregnancy. During pregnancy, the body goes through various anatomical and physiological changes to provide suitable environment for foetal development, to cater to the increased metabolic demands and to prepare for the childbirth. These changes have notable anaesthetic implications in determining the optimal anaesthetic technique, while also keeping in mind the gestational age, type of procedure and any coexisting medical condition. A randomized controlled trial was done among 200 pregnant women in Department of Obstetrics and Gynaecology at Tertiary care institute and hospital for the period of 6 months (November 2021 to April 2022). The physiology of the respiratory system changes continuously during pregnancy. Due to the effects of progesterone on bronchial smooth muscle, airway resistance is reduced by 50%. The Minute ventilation, RR, Tidal volume, and Alveolar ventilation are increased. Anatomically, diaphragm moves up with cephalad pressure of the growing gravid uterus, and the chest wall diameter increases in both anteroposterior and transverse diameters. This leads to unchanged Total Lung Capacity, Vital Capacity, and CC, while Expiratory Reserve Volume, Residual volume, and Functional residual capacity seen a decrease in 20% in all patients. Blood volume increases rapidly early in pregnancy (around 12 weeks), then gradually increases during the second trimester and then more slowly throughout the pregnancy. Cardiac output rises early in pregnancy, with changes detectable by 8 weeks. Increased minute ventilation, RR, tidal volume, and alveolar ventilation. Cardiac output rises early in pregnancy, with changes detectable by 8 weeks. Cardiac output rises most rapidly (to approximately 35% above baseline) during the second trimester and then stays relatively constant until term. With labour contractions, output increases significantly; each contraction increases cardiac output by 10-25%.